Confronting our Agricultural Nonpoint Source Control Policy Problem. (7th June 2022) - Stephenson, Kurt; Shabman, Leonard; Shortle, James; Easton, Zachary
Abstract: Federal and state agricultural and environmental agencies have spent enormous sums since the 1990s to reduce nonpoint source (NPS) water pollution from agriculture. Yet, water quality problems are pervasive, and agriculture is a major cause. The lack of progress is often attributed to insufficient funding for pollution control practices relative to the scale of the problem. However, we attribute the lack of progress to shortcomings in agricultural NPS pollution control policy. We illustrate our argument after considering nearly four decades of federal, state, and local efforts to reduce agricultural NPS pollution to the Chesapeake Bay. Additional funding for current programs, absent fundamental program reform, is unlikely to produce reductions from agriculture needed to achieve desired water quality outcomes. Abstract : Research Impact Statement : Reform of agricultural nonpoint source pollution policies is necessary to make progress in achieving water quality goals.